Investigation of the Effect of Temperature on the Structure of the Polyacrylic Acid Adsorption Layer at a Controlled Porosity Glass/Polymer Solution Interface - Malgorzata Wiśniewska (Adsorption Science & Technology)
The influence of temperature on the structure of polyacrylic acid (PAA) adsorption layers on the surface of controlled porosity glass (CPG) was studied. For this purpose, adsorption, surface charge, zeta potential and viscosity measurements were carried out over the 15–35°C temperature range. The amounts of adsorbed polymer and the thickness of the polymer adsorption layer increase with increasing temperature. This is caused by conformational changes in the polymer macromolecules with increasing temperature, changing from a coiled structure at lower temperature to a more stretched structure at higher temperature. The free energies of the PAA segments adsorbed onto the CPG surface at 25°C were calculated from the adsorption data. Decreases in the charges on the surface and diffuse layers of CPG particles were observed in the presence of PAA. On the basis on these data, proposals have been made regarding the main factors causing the changes in the zeta potential and surface charge of CPG in the presence of polymer.